2018
DOI: 10.1017/s1041610217002885
|View full text |Cite
|
Sign up to set email alerts
|

Does the community-based combined Meeting Center Support Programme (MCSP) make the pathway to day-care activities easier for people living with dementia? A comparison before and after implementation of MCSP in three European countries

Abstract: This study shows that MCSP fills (part of) the gap between diagnosis and residential care and can therefore be seen as a pillar of post-diagnostic care and support. Further dissemination of Meeting Centers in Europe may have a multiple impact on the structure of dementia services in European countries and the pathways to day care for people with dementia and their carer(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…The analysis also undertook numerous tests of significance and multiple comparisons. However, the current study was designed primarily as an implementation study where much of the time and energy was put in realising at least 2 MCs in each country who provided the full MCSP were piloted and evaluated. Consequently, larger samples with blind assessment were not possible in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis also undertook numerous tests of significance and multiple comparisons. However, the current study was designed primarily as an implementation study where much of the time and energy was put in realising at least 2 MCs in each country who provided the full MCSP were piloted and evaluated. Consequently, larger samples with blind assessment were not possible in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Materials and concepts developed in the Netherlands were translated. Compliance with the original MCSP model was maintained to a high degree, although several country adaptations were made, such as more flexibility of attendance to the programme according to need, severity of dementia of the target group, and additional therapeutic approaches . The MC “club” was offered 3 days per week in the UK and Poland and 3 half‐days to 2 days per week in Italy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland, there is a lack of a multidisciplinary, coordinated system of care for people with dementia in the form of an evidence-based structured pathway 11. The post-diagnostic support is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Reductions in length of stay and readmission were found as a consequence of type of added support. In a multi-center European study, reported by Szcześniak et al (2018), the introduction of new meeting centers as a bridge between diagnosis and residential care was evaluated in four countries. The intervention proved successful in providing more structured care pathways and post-diagnostic support for people with dementia and their carers.…”
mentioning
confidence: 99%